2018
DOI: 10.3390/ijms19082462
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of 2-Deoxyglucose Side Effects by Ketogenic Diet

Abstract: Cancer metabolism is characterized by extensive glucose consumption through aerobic glycolysis. No effective therapy exploiting this cancer trait has emerged so far, in part, due to the substantial side effects of the investigated drugs. In this study, we examined the side effects of a combination of isocaloric ketogenic diet (KD) with the glycolysis inhibitor 2-deoxyglucose (2-DG). Two groups of eight athymic nude mice were either fed a standard diet (SD) or a caloric unrestricted KD with a ratio of 4 g fat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…3 K ). On subjective examination, mice receiving 2-DG alone did not appear sick but those showing the lowest activity post-2-DG tended to be those showing the highest levels of glucose, perhaps suggesting that blocking glucose utilization (functionally similar to hypoglycemia) could increase blood glucose but still produce inactivity as has been shown with higher doses of 2-DG ( Voss et al, 2018 ).…”
Section: Resultsmentioning
confidence: 86%
“…3 K ). On subjective examination, mice receiving 2-DG alone did not appear sick but those showing the lowest activity post-2-DG tended to be those showing the highest levels of glucose, perhaps suggesting that blocking glucose utilization (functionally similar to hypoglycemia) could increase blood glucose but still produce inactivity as has been shown with higher doses of 2-DG ( Voss et al, 2018 ).…”
Section: Resultsmentioning
confidence: 86%
“…Some of the completed trials even showed promising and exciting results. Given the side effects of some metabolic regulators [219], the role of metabolism targeted therapy in nonmalignant tissues should also be emphasized in future research, which largely restricts the transformation from basic study to successful clinical application. Moreover, pancreatic cancer displayed highly plastic metabolism, suggesting that cancer cells can adapt to use other metabolic pathways to bypass a [220].…”
Section: Clinical Perspectives and Conclusionmentioning
confidence: 99%
“…Recent research has focused on exploring those agents that can potentially inhibit the action of HKII, thereby inhibiting the function of glucose metabolism. For example, 2-deoxy- d -glucose (2-DG) and 3-bromopyruvate (3-BP) are the common synthetic mitocans that exhibit their cytotoxic effect on the cancer cells by inhibiting the HKII [ 63 , 64 ]. Benserazide is another mitocan that selectively inhibits HKII by specifically binding to HKII and inhibiting the enzymatic activity of HKII.…”
Section: Mitocans: the Alternative Cancer Therapymentioning
confidence: 99%